Las garantías jurisdiccionales para la tutela judicial efectiva de los derechos de los animales desde el principio de diversidad ecológica - Bolaños, María F. (2023)
The study aimed to analyze jurisdictional guarantees as a means for effective judicial protection of animal rights, from the principle of ecological diversity. Initially, a presentation of the background of the research was made, exploring the theoretical, regulatory, and jurisprudential bases related to animal rights. Next, the constitutional and jurisdictional guarantees were analyzed, including various legal actions that can be used to safeguard the rights of animals. Subsequently, the protection of animal rights in Ecuador was examined from the perspective of jurisdictional guarantees, evaluating its applicability, access to justice and the specific rights of animals. Additionally, the precautionary measures that can be taken for the benefit of animals were mentioned, making special reference to the use of habeas corpus, for which the case of “Monita Estrella” was analyzed. Finally, as the main conclusion of the research, animals, being part of nature, are subjects of rights within the legal system of Ecuador; Highlighting food, life, specialized veterinary care, comprehensive respect for their existence, among others. Given this, in the Constitutional State for each one there is a jurisdictional guarantee that protects them.